2020
DOI: 10.1002/jaba.780
|View full text |Cite
|
Sign up to set email alerts
|

A translational comparison of contingency‐based progressive delay procedures and their effects on contextually appropriate behavior

Abstract: Schedule thinning is an essential step in treating problem behavior, yet little research has been conducted to determine the method associated with sustained treatment effects. A frequently used method for thinning reinforcement is contingency‐based progressive delay, which requires the individual to meet some criteria before the reinforcers are returned. The response requirement could be dependent on (a) contextually appropriate behavior (differential reinforcement of alternative behavior‐based thinning) or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Recent single-subject comparative analyses have revealed more favorable outcomes-with respect to challenging behavior reduction and replacement skill acquisition-when RST involved contingency-based delays as opposed to time-based delays (Drifke et al, 2020;Ghaemmaghami et al, 2016). Furthermore, Iannaccone and Jessel (2021) found that contextually appropriate behavior was more likely to be acquired and maintained when contingency-based RST procedures were DRAbased as opposed to DRO-based. Therefore, given the somewhat recent emergence of novel contingency-based delay procedures, the finding that studies evaluating intensive behavioral interventions for individuals with ASD tend to report only short-term effects (Rodgers et al, 2021), and the understanding that RST is critical to the sustained success of behavioral interventions supporting the needs of individuals with ASD (Galpin et al, 2018;Ghaemmaghami et al, 2021;Hagopian et al, 2011), the current meta-analytic review contributes directly to the literature to illustrate that contingency-based RST procedures have produced robust and durable intervention outcomes across heterogeneous intervention contexts.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Recent single-subject comparative analyses have revealed more favorable outcomes-with respect to challenging behavior reduction and replacement skill acquisition-when RST involved contingency-based delays as opposed to time-based delays (Drifke et al, 2020;Ghaemmaghami et al, 2016). Furthermore, Iannaccone and Jessel (2021) found that contextually appropriate behavior was more likely to be acquired and maintained when contingency-based RST procedures were DRAbased as opposed to DRO-based. Therefore, given the somewhat recent emergence of novel contingency-based delay procedures, the finding that studies evaluating intensive behavioral interventions for individuals with ASD tend to report only short-term effects (Rodgers et al, 2021), and the understanding that RST is critical to the sustained success of behavioral interventions supporting the needs of individuals with ASD (Galpin et al, 2018;Ghaemmaghami et al, 2021;Hagopian et al, 2011), the current meta-analytic review contributes directly to the literature to illustrate that contingency-based RST procedures have produced robust and durable intervention outcomes across heterogeneous intervention contexts.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…skills) in order to produce that same reinforcement. The behavioral expectations of the child during the contingency-based delay can be programmed to vary in three possible ways (Iannaccone & Jessel, 2021). First, a negative contingency can be arranged whereby reinforcers will be returned following the absence of challenging behavior.…”
mentioning
confidence: 99%
“…Differential reinforcement of other behaviors (DRO) is one of such interventions termed contingency management [ 15 , 21 23 ]. It involves actively and positively reinforcing tic suppression in a subject by providing small reinforcers (e.g., tokens or small amounts of money) in exchange for progressively longer periods of successful tic suppression [ 24 ]. This reinforces a competing response that is performed prior to the occurrence of the tic, thus interrupting it [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps one of the most recent examples of leading with compassionate care has been the work of Hanley and colleagues as it relates to the Practical Functional Assessment (Hanley et al, 2014), Skills Based Treatment (Ghaemmaghami et al, 2015;Iannaccone & Jessel, 2021), and the use of Universal Protocols (Ghaemmaghami et al, 2016;Rajaraman et al, 2022). These procedures are described as ways to implement behavior analytic principles while being guided by compassion and trauma-informed care.…”
Section: Introductionmentioning
confidence: 99%